Diurnal variation of rainfall in Northern Luzon - ARIEL, ZAMUDIO (Archīum Ateneo, 2011)
The diurnal variation of rainfall in Northern Luzon is described by discussing the role of topography and local wind systems during three different monsoon periods in three different years using observation data from PAGASA-DOST. Baguio, which is a mounta